The Efficacy and Safety of an Ayurvedic Petsaffa Formulation in Subjects with Constipation: An Open-Label, Non-Randomized Clinical Study (International Journal of Ayurveda and Pharma Research, 2023)
Constipation is a common gastrointestinal complaint among 16% of the world's population. Several conventional treatments are recommended; however, these sometimes do not provide satisfactory results for many patients or cause unpleasant side effects. In this context, Ayurvedic medicine can be an alternative, cost-effective and satisfactory treatment for constipation. Hence, this clinical study aimed to evaluate the efficacy and safety of an Ayurvedic PetSaffa formulation in subjects with functional constipation. Design, Setting, Participants and Intervention: This open-label, non-randomized clinical study was conducted to evaluate the safety and efficacy of an Ayurvedic PetSaffa formulation in healthy volunteers with functional constipation. Subjects were selected based on inclusion and exclusion criteria. Participants received PetSaffa granules for 21 days. Outcome parameters of the study, including frequency of bowel movements, constipation score, constipation symptoms, gas, acidity, and serum level of SGPT, were evaluated at screening and after 21 days of treatment. Results: A total of 120 participants completed the 21-day treatment. At the end of the treatment period, all clinical outcomes, including frequency of bowel movement and constipation score, were significantly (p